Números complexos e equações algébricas - Lima, Ítalo Renan Lacerda (2022)
The present work aims to show what are the algebraic equations and the numbers complex and how they can help in understanding some problems of basic education and higher. First, we approach the historical aspects of the origin of this set and how mathematicians of that time struggled over its acceptance. in a second For now, we define complex numbers and their properties and show the various forms that these numbers can take, which can range from an algebraic representation to a matrix representation. Then we define the algebraic equations and show the importance of the theory around the equations, with the purpose of establishing foundations for the complex numbers. Finally, the work shows some applications of complex numbers that pass through subjects from high school to higher education.